Negotiating cohesion : uncomfortable positions in local government - Jones, Hannah (The Policy Press, 2013)
Using original empirical data, this book explores how local government officers and politicians negotiate 'difficult subjects' linked with community cohesion policy: diversity, inequality, discrimination, extremism, migration, religion, class, power and change.